Reflections on using Talanoa methodology to engage with Pacific youth in Aotearoa New Zealand about their sexual and reproductive health - Radilaite Cammock; Tengihia Pousini; Malcolm Andrews (Sexual and Reproductive Health Matters)
Pacific understandings of sexual and reproductive health (SRH) encompass beliefs and practices reflective of Pacific values systems. These are integral to cultural understandings of safety, relationships, and intimacy. Research processes and practices that appropriately address these values and sensitivities are scarcely available in the literature, leading to limited use and understanding of culturally appropriate methods and procedures. Pacific methodologies like Talanoa are useful in ensuring that cultural perspectives unique to Pacific youth are addressed and appropriately represented in the research. This paper describes how cultural factors associated with sexual and reproductive health influenced the Talanoa research processes in a study of Pacific youth and SRH education. Key cultural considerations are discussed focussing on the positionality of the researchers, cultural sensitivities and protocols, communication strategies and the role of flexibility in privileging Pacific youth voices.